Patrarkhi dalam Sistem Keluarga Muslim Tradisional - Rahmawati Baharudin (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
The system of patriarchy has a minor view on women who are considered as subordinated to men due to their lack of intelligence. Religious texts interpreted from androcentric point of view, local culture of Arabian society of the middle age, and the influence of social system of Persians and romans are responsible in perpetuating the system patriarchy. By emphasizing universal concept of the Quran on justice, equality and harmony, this article aims to repudiate the argument of patriarchy which permeates traditional Muslim social system. This article also critically examines misogynic hadith on fitna, absolute surrender and lack of intelligence of women of wife, upon which patriarchal authority and women subordination is based.